Eddy stirring and horizontal diffusivity from Argo float observations : geographic and depth variability - Cole, Sylvia T.; Wortham, Cimarron J. L.; Kunze, Eric; Owens, W. Brechner (Geophysical Research Letters, 2015)
Author Posting. © American Geophysical Union, 2015. This article is posted here by permission of American Geophysical Union for personal use, not for redistribution. The definitive version was published in Geophysical Research Letters 42 (2015): 3989–3997, doi:10.1002/2015GL063827. Stirring along isopycnals is a significant factor in determining the distribution of tracers within the ocean. Salinity anomalies on density surfaces from Argo float profiles are used to investigate horizontal stirring and estimate eddy mixing lengths. Eddy mixing length and velocity fluctuations from the ECCO2 global state estimate are used to estimate horizontal diffusivity at a 300 km scale in the upper 2000 m with near-global coverage. Diffusivity varies by over two orders of magnitude with latitude, longitude, and depth. In all basins, diffusivity is elevated in zonal bands corresponding to strong current regions, including western boundary current extension regions, the Antarctic Circumpolar Current, and equatorial current systems. The estimated mixing lengths and diffusivities provide an observationally based data set that can be used to test and constrain predictions and parameterizations of eddy stirring. This work was supported by the National Science Foundation under grants OCE-13-55668 and OCE-95-21468 and the Office of Naval Research under grants N00014-12-1-0336 and N00014-13-1-0484. 2015-11-21